Serum Procalcitonin in Chronic Obstructive Pulmonary Disease - Farzaneh Akbari; Mina Delghandi; Fariba Rezaeetalab (Reviews in Clinical Medicine, 2021)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide. One of the most important events in the course of COPD is acute exacerbation. Acute exacerbation of COPD (AECOPD) is characterized by the aggravation of dyspnea, cough, and sputum. Chronic obstructive pulmonary disease exacerbation leads to respiratory failure, hospitalization, morbidity, and mortality. During and after the COPD attack, lung function dramatically decreased.  Bacterial pneumonia is an important and serious risk factor for AECOPD. However, there are other inflammatory and non-inflammatory causes of AECOPD. Antibiotic treatment is usually challenging in AECOPD. Procalcitonin is a non-hormone active protein and precursor to calcitonin that consists of 116 amino acids, and 13 kDa weight is produced by the neuroendocrine cells of the thyroid gland. However, procalcitonin is secreted in septic shock, metastatic cancers, bacterial and fungal infections; therefore, serum procalcitonin is increased in bacterial pneumonia of AECOPD. Some studies recommended procalcitonin serum measurement as a guide for antibiotic initiation in AECOPD.